Pengaruh Akuntansi Hijau, Ukuran Perusahaan dan Pengungkapan Media Terhadap Pengungkapan Corporate Social Responsibility - Lola Cyhintia; Efrizal Sofyan (Jurnal Eksplorasi Akuntansi, 2023)
This is the quantitative study that aims to determine the effect of green accounting, firm size and media exposure to corporate social responsibility disclosure. The population in this study is a property and real estate companies listed on the Indonesian Stock Exchange (IDX ) in 2018-2021. The sample in this study was taken using the purposive sampling method with a total sample is 124 samples for a 4 year statement period. The secondary data types were used in this study, which were obtained from the IDX and companies official website. This study used multiple linear regression analysis. The results of this analysis imply that (1). Green Accounting has a positive effect on corporate social responsibility disclosure. (2). Firm Size has a positive effect on corporate social responsibility. (3). Media Exposure has no effect on corporate social responsibility.This is the quantitative study that aims to determine the effect of green accounting, firm size and media exposure to corporate social responsibility disclosure. The population in this study is a property and real estate companies listed on the Indonesian Stock Exchange (IDX ) in 2018-2021. The sample in this study was taken using the purposive sampling method with a total sample is 124 samples for a 4 year statement period. The secondary data types were used in this study, which were obtained from the IDX and companies official website. This study used multiple linear regression analysis. The results of this analysis imply that (1). Green Accounting has a positive effect on corporate social responsibility disclosure. (2). Firm Size has a positive effect on corporate social responsibility. (3). Media Exposure has no effect on corporate social responsibility.